AB0174 Tnf-Α modulates microglia activation via nf-Κb activity in systemic lupus erythematosus with depression. (12th June 2018) - Kong, X.; Shen, K.; Ji, J.; Fu, T.; Yang, J.; Gu, Z.
Abstract : Background: Systemic lupus erythematosus (SLE) is a complex autoimmune disease accompanied by damage to a variety of tissue injuries, such as joints, kidney, and the peripheral and central nervous systems (CNS). 1 The diffuse CNS lupus manifests with a diverse array of neuropsychiatric symptoms that range from headaches, anxiety, depression, to cognitive impairment and, in rare cases, psychosis. 2 Additionally, up to 24% of SLE patients will display depression. 3 Previus studies have suggested microglia, as critical mediators of depression in SLE. Objectives: To date, the pathophysiology of most depression symptoms in SLE has not been well determined. We focused our attention on the potential role of microglia in neuroinflammation in SLE patients. Methods: Cerebrospinal fluid was collected from 3 healthy people and 3 SLE patients. According to the hospital anxiety and depression scale (HADS), we investigate the depression of SLE patients. The cytokines were screened using a RayBio Human Cytokine Antibody Array in cerebrospinal fluid samples by analysing a variety of inflammatory cytokines such as IL-6, Leptin and TNF-α. Cerebrospinal fluid of SLE patients and normal people were tested by ELISA for TNF-α. The depression status of MRL/lpr (C3MRL-Faslpr/J) mice and Balb/c mice was determined by tail suspension test, open-field test and sucrose preference test. Immunofluorescence and Western blot was utilised to detect the activation of microglial cells in brain tissue. Microglia cells were stimulated by TNF-α, Western blot showed the expression of CD68 and activated NF-κB. The concentrations of IL-6 and IL-1β in the cell supernatants were measured by ELISA. After using of NF-КB signalling pathway inhibitor PDTC, the activation of microglia stimulated by TNF-α was determined by immunofluorescence, quantitative PCR, Western blot analysis and ELISA. Results: The results showed that the level of TNF-α in cerebrospinal fluid of patients with lupus was higher than normal people. At 14 weeks, MRL/lpr mice appear depression by tail suspension test, open-field test and sucrose preference test, MRL/lpr mice had more reactive microglia in the cortex when compared to Balb/c. After microglial cell were stimulated by TNF-α, microglias were active and effectively release IL-6, IL-1β and iNOS. Moreover, the expression of CD68 and activated NF-κB signalling pathway were also higher significantly. However, the use of NF-κB signalling pathway inhibitor PDTC reverse the TNF-α induced microglial activation. Conclusions: The study showed that the different level of inflammatory cytokines of cerebrospinal fluid of SLE patients. Our results highlight the potential role of microglia in neuroinflammation in SLE patients with depression. References: [1] Bialas AR, et al. Microglia-dependent synapse loss in type I interferon-mediated lupus. Nature2017. [2] McHugh J. Systemic lupus erythematosus: IFN drives synapse loss via microglia. Nat Rev Rheumatol2017;13(8):449. [3] Zhang L, et al. Prevalence of depression and anxiety in systemic lupus erythematosus: a systematic review and meta-analysis. BMC Psychiatry2017;17(1):70. Acknowledgements: This work was supported by grants from The Natural Science Foundation of China under Grant (81401124)and The Natural Science Foundation of China under Grant (8167060931). Disclosure of Interest: None declared